2017
DOI: 10.1111/evo.13394
|View full text |Cite
|
Sign up to set email alerts
|

Repeated evolution and reversibility of self‐fertilization in the volvocine green algae*

Abstract: Outcrossing and self-fertilization are fundamental strategies of sexual reproduction, each with different evolutionary costs and benefits. Self-fertilization is thought to be an evolutionary "dead-end" strategy, beneficial in the short term but costly in the long term, resulting in self-fertilizing species that occupy only the tips of phylogenetic trees. Here, we use volvocine green algae to investigate the evolution of self-fertilization. We use ancestral-state reconstructions to show that self-fertilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
83
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(94 citation statements)
references
References 98 publications
(145 reference statements)
10
83
1
Order By: Relevance
“…They found that specialization was less detrimental than expected: only two phylogenies showed significant reduction in diversification and higher “tippiness.” Similarly, Hanschen et al. () show that selfing did not seem to be a dead‐end trait (corroborated by the two reversals from selfing to outcrossing). Bromham et al.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…They found that specialization was less detrimental than expected: only two phylogenies showed significant reduction in diversification and higher “tippiness.” Similarly, Hanschen et al. () show that selfing did not seem to be a dead‐end trait (corroborated by the two reversals from selfing to outcrossing). Bromham et al.…”
mentioning
confidence: 78%
“…Hanschen et al. () suspected that certain species have only recently evolved selfing, and descend from outcrossing ancestors. By investigating the evolution of self‐fertilization, they hoped to see how often selfing had evolved, how long it persisted, and if selfing species are concentrated on the tips of the evolutionary tree.…”
mentioning
confidence: 99%
See 3 more Smart Citations